Meningkatkan Kemampuan Literasi Informasi Mahasiswa dengan Pembentukan Academic Information Literacy Class di Perpustakaan Universitas Riau - Evi Susanti; Thamrin Hasan (Jurnal Gema Pustakawan, 2026)
Technological developments and the penetration of Artificial Intelligence (AI) have triggered the phenomenon of information overload and information anxiety among students. On the other hand, the utilization of digital assets at the University of Riau Library is still relatively low, thus triggering low-quality references and a high risk of plagiarism in student scientific papers. This study aims to describe the design, implementation strategy, and core materials of the "Academic Information Literacy Class" as a structured intervention step by the library. The program implementation method applies a Blended Learning and Project-Based Learning approach based on the Outcome-Based Education (OBE) curriculum. The core learning materials are focused on three main operational pillars: advanced scientific information retrieval techniques, strategies for selecting reputable journal publication media, and education on the legal and ethical use of AI in preparing research proposals. The analysis results show that the establishment of this structured class has proven effective in improving research independence, the quality of scientific writing, and student awareness of academic integrity. Through this program, the University of Riau Library has successfully adaptively transformed its role from merely a place to store physical collections (book repository) to a driver of academic quality (research facilitator).